(untitled) (Journal of the College of Basic Education, 2025)
In this work, we identified two operators of type and , where is below the function and is the above the function . In this paper, the aim of it is to study and for a few unbounded functions, find the level of the most accurate approximation in the multiplier space and we obtained results.